2015
DOI: 10.1007/s11743-015-1688-4
|View full text |Cite
|
Sign up to set email alerts
|

Complexation of Surfactant/β‐Cyclodextrin to Inhibit Surfactant Adsorption onto Sand, Kaolin, and Shale for Applications in Enhanced Oil Recovery Processes. Part I: Static Adsorption Analysis

Abstract: Surfactant adsorption onto solid surfaces is a major issue during surfactant flooding in enhanced oil recovery applications; it decreases the effectiveness of the chemical injection making the process uneconomical. Therefore, it was hypothesized that the adsorption of surfactant onto solid surfaces could be inhibited using a surfactant delivery system based on the complexation between the hydrophobic tail of anionic surfactants and b-cyclodextrin (b-CD). Proton nuclear magnetic resonance spectroscopy was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…In all cases, the t statistic for related samples analysis indicated that the use of the SDS/β‐CD inclusion complex significantly inhibits the adsorption of surfactant onto the solid adsorbents with adsorption reductions ranging from 64–71 % as indicated by Figure . These observations validate previous observations …”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…In all cases, the t statistic for related samples analysis indicated that the use of the SDS/β‐CD inclusion complex significantly inhibits the adsorption of surfactant onto the solid adsorbents with adsorption reductions ranging from 64–71 % as indicated by Figure . These observations validate previous observations …”
Section: Resultssupporting
confidence: 93%
“…Several mechanisms have been proposed in our previous research to explain the significant adsorption inhibition of the surfactant onto solid surfaces . These mechanisms include steric hindrance due to the encapsulation of the hydrophobic surfactant tail into the β‐CD cavity that disrupts the formation of surface aggregates or hemimicelles, by interfering with the packing of surfactant molecules in the adsorbed layer and laterally between adsorbed surfactants.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations